The phloem as a mediator of plant growth plasticity - López-Salmerón, Vadir; Cho, Hyunwoo; Tonn, Nina; Greb, Thomas (Current biology, 2019)
Developmental plasticity, defined as the capacity to respond to changing environmental conditions, is an inherent feature of plant growth. Recent studies have brought the phloem tissue, the quintessential conduit for energy metabolites and inter-organ communication, into focus as an instructive developmental system. Those studies have clarified long-standing questions about essential aspects of phloem development and function, such as the pressure flow hypothesis, mechanisms of phloem unloading, and source-sink relationships. Interestingly, plants with impaired phloem development show characteristic changes in body architecture, thereby highlighting the capacity of the phloem to integrate environmental cues and to fine-tune plant development. Therefore, understanding the plasticity of phloem development provides scenarios of how environmental stimuli are translated into differential plant growth. In this Review, we summarize novel insights into how phloem identity is established and how phloem cells fulfil their core function as transport units. Moreover, we discuss possible interfaces between phloem physiology and development as sites for mediating the plastic growth mode of plants.
Gesehen am 27.03.2019